Efficacy of antiseptics and chemomechanical methods for dentin caries lesions: A systematic review with GRADE approach - Ferreira, Luiza de Almeida Queiroz; Diniz, Ivana Márcia Alves; Peixoto, Rogéli Tibúrcio Ribeiro da Cunha; Gomes, Natália Aparecida; Caneschi, Camila de Sousa; Spineli, Loukia Maria; Martins, Carolina Castro (Frontiers in Oral Health, 2023)
Objectives: Selective caries removal aims to remove carious tissue in deep dentin lesions. However, a discussion stands on the value of antiseptics and chemomechanical adjuvant methods to reduce the bacterial load on residual caries lesions. This systematic review has addressed two main clinical questions to compare the antimicrobial efficacy of available methods using (1) antiseptic or (2) chemomechanical agents before restoring dentin carious lesions. Methods: We included randomized and non-randomized controlled trials (RCTs/ NRCTs). We searched eight databases from inception to October 2021. Paired reviewers independently screened studies, extracted data, and assessed the risk of bias. The primary outcome was the reduction in the number of total bacterial in dentin, whereas secondary outcomes were reduction in the number of Lactobacillus and Streptococcus. We used the ratio of ratio of post-treatment to baseline means between two interventions in the logarithmic scale as a proper effect measure. Certainty of evidence was assessed with the Grading of Recommendations, Assessment, Development and Evaluation approach. Results: We included 14 RCTs and 9 NRCTs, with nine interventions. Regardless the method, the number of bacteria at baseline was similar or exceeded that after the intervention, particularly in NRCTs. The evidence was inconclusive for most comparisons. Among antiseptic agents, chlorhexidine (CHX) resulted in an average of 1.14 times [95% confidence interval (CI): 1.08 – 1.21] more total bacterial than photodynamic therapy in RCTs. Among NRCTS, the natural agents resulted in five times more total bacterial than CHX (95% CI: 2 – 11). For chemomechanical methods, the control resulted in eight times (95% CI: 4 – 17) more total bacterial than Carisolv (SHAA). Conclusions: The certainty of the evidence was very low for all comparisons showing uncertainty whether one treatment could be more effective than another for dentin disinfection. So far, exclusively removing soft carious dentin would be enough to reduce the bacterial count.